Hubungan Umur dan Paritas Ibu dengan Pemilihan Metode Kontrasepsi Jangka Panjang di Klinik Rawat Inap Vita Medika Kepung Kabupaten Kediri Tahun 2017 - Sulistijowati Sulistijowati; Siti Asiyah; Brivian Florentis Yustanta (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2018)
Indonesia's population growth rate is still relatively high, within a year the population of Indonesia increases by around 4 million. In order to control fertility, the government promotes long-term contraceptive methods including at the Inpatient Vita Medika Kepung Kediri Clinic. Objective To determine the relationship between maternal age and parity with the selection of long-term contraceptive methods at the Vita Medika Nursing Clinic in Kepung Kediri. Research Method Analytical Correlational research design with Kohort retrospective time. The population in this study were all KB acceptors at the Vita Medika Kepung Inpatient Clinic in Kediri. The sample technique uses proportional random sampling, in this study a sample of 99 acceptors was obtained. The tool used is a cohort. Data analysis using Chi-Square test. Results: In the use of long-term contraceptive methods, acceptors pay more attention to age factors than parity, with a chi-square coefficient of 0.04 and parity having a chi-square coefficient of 0.075, with a value of 0.05, so that the relationship between age and Long Term Contraception Method selection and the absence of a relationship between parity and Long Term Contraception Method selection at Vita Medika Kepung Inpatient Clinic in Kediri. There is a relationship between age andLong Term Contraception Method selection and there is no relationship between parity and Long Term Contraception Method in the Vita Medika Kepung Inpatient Inpatient Clinic. It is expected that acceptors in the use of contraceptives can correctly use contraceptive methods as needed according to various factors.